Genetic characterization of Northern Flints and Flours maize (Zea mays L. spp. mays) with isozyme, SSR, and morphological markers - González Ugalde, William Gerardo ([editor no identificado], 1997)
Tesis ( Doctor of Philosophy)--Iowa State University, 1997.